Edukasi Penatalaksanaan Nyeri Haid pada Remaja Putri dengan Terapi Akupresur di Posyandu Remaja - Defri Novitasari; Widayati; Joeleha; Riska Dayang Safitri; Eva Rizqi Arti; Umi Bekti Iriana; Yuli Ariyanti; Lincayanti, Titiek Nur (Universitas Ngudi Waluyo, 2025)
Menstruation is periodic and cyclical bleeding from the uterus accompanied by the release (desquamation) of the endometrium. Menstrual problems that often occur in adolescent girls are menstrual pain (dysmenorrhea). The prevalence of dysmenorrhea reached 72.89% in Indonesia. Menstrual pain causes adolescents to be easily tired and lackluster, as well as difficulty concentrating due to discomfort which reduces the quality of life of adolescent girls. One of the non-pharmacological therapies that can be done to overcome menstrual pain is acupressure. The purpose of community service in Srinahan village, Kesesi is to increase the knowledge of adolescent girls to overcome menstrual pain with acupressure techniques. The community service includes 5 steps: 1) Finding respondents, 2) conducting pretest, 3) counseling on training and simulation of acupressure techniques, 4) posstest, 5) evaluation. The results after the education on acupressure techniques showed the level of knowledge of adolescent girls with the category of sufficient knowledge as much as 29.4% and good knowledge as much as 70.6%. The results of this community service show an increase in the knowledge of adolescent girls after being given education about handling menstrual pain with acupressure techniques. Acupressure technique is an effective nonpharmacological therapy to reduce menstrual pain in adolescent girls. Abstrak Menstruasi merupakan pendarahan periodik dan siklus dari rahim yang disertai dengan pelepasan (deskuamasi) endometrium. Masalah menstruasi yang sering terjadi pada remaja perempuan yaitu nyeri haid (dismenore). Prevalensi dismenore mencapai 72,89% di Indonesia. Nyeri haid mengakibatkan remaja mudah lelah dan kurang bersemangat, serta kesulitan berkonsentrasi karena ketidaknyamanan yang menurunkan kualitas hidup remaja putri. Salah satu terapi nonfarmakologis yang dapat dilakukan untuk mengatasi nyeri haid adalah akupresur. Tujuan dilakukan pengabdian masyarakat di desa Srinahan, Kesesi yaitu untuk meningkatkan pengetahuan pada remaja putri untuk mengatasi nyeri haid dengan teknik akupresur. Metode yang digunakan dalam pengabdian masyarakat meliputi 5 langkah : 1) Mencari responden, 2) melakukan pretest, 3) penyuluhan tentang pelatihan dan simulasi teknik akupresure, 4) posstest, 5) evaluasi. Hasil sesudah dilakukan edukasi tentang teknik akupresur menunjukkan tingkat pengetahuan remaja putri dengan kategori pengetahuan cukup sebanyak 29,4% dan pengetahuan baik sebanyak 70,6%. Hasil pengabdian masyarakat ini memperlihatkan adanya peningkatan pengetahuan remaja putri sesudah diberikan edukasi tentang penanganan nyeri haid dengan Teknik akupresur. Diharapkan dengan pemberian edukasi teknik akupresur dapat menjadi terapi nonfarmakologis yang efektif untuk menurunkan nyeri haid pada remaja putri.